Pembinaan Kesadaran Hukum Peserta Didik melalui Metode Pembelajaran Role-Playing di Kelas VII SMP Negeri 5 Garut - Tira Cantika; Syfa Kaila Damayanti; Ulpa Dwi Martiani Martiani; Valerie Nadya Stien; Tetep Tetep (Cipta Media Harmoni, 2025)
The urgency of this research is based on the low legal awareness among junior high school students, which is reflected in the still rampant violations of school rules and low understanding of legal norms. The purpose of this study is to increase the legal awareness of students in class VII-H of SMP Negeri 5 Garut. The method used is through role-playing on the material